High-performance parallel database processing and grid databases - Taniar, David; Leung, Clement H. C.; Rahayu, Johanna Wenny (Wiley, 2008)
"The growth in grid databases, coupled with the utility of parallel query processing, presents an important opportunity to understand and utilize high-performance parallel database processing within a major database management system (DBMS). This important new book provides readers with a fundamental understanding of parallelism in data-intensive applications, and demonstrates how to develop faster capabilities to support them. It presents a balanced treatment of the theoretical and practical aspects of high-performance databases to demonstrate how parallel query is executed in a DBMS, including concepts, algorithms, analytical models, and grid transactions." -- Publisher's description.
Keywords: High performance computing; Parallel processing (Electronic computers); Computational grids (Computer systems); Grid Computing; Paralleles Datenbanksystem